A Metal–Organic Framework with Suitable Pore Size and Specific Functional Sites for the Removal of Trace Propyne from Propylene. (15th October 2018) - Li, Libo; Wen, Hui‐Min; He, Chaohui; Lin, Rui‐Biao; Krishna, Rajamani; Wu, Hui; Zhou, Wei; Li, Jinping; Li, Bin; Chen, Banglin
Abstract: Separation of propyne/propylene (C3 H4 /C3 H6 ) is more difficult and challenging than that of acetylene/ethylene (C2 H2 /C2 H4 ) because of their closer molecular sizes. A comprehensive screening of a series of metal–organic frameworks with broad types of structures, pore sizes, and functionalities was carried out. UTSA‐200 was identified as the best separating material for the removal of trace C3 H4 from C3 H4 /C3 H6 mixtures. Gas sorption isotherms reveal that UTSA‐200 exhibits by far the highest C3 H4 adsorption capacity (95 cm 3 cm −3 at 0.01 bar and 298 K) and record C3 H4 /C3 H6 selectivity, which was mainly attributed to the suitable dynamic pore size to efficiently block the larger C3 H6 molecule whilst the strong binding sites and pore flexibility capture smaller C3 H4 . This material thus provides record purification capacity for the removal of C3 H4 from a 1:99 (or 0.1:99.9, v/v) C3 H4 /C3 H6 mixture to produce 99.9999 % pure C3 H6 with a productivity of 62.0 (or 142.8) mmol g −1 .